High-Throughput Computational Investigation of Homogeneous and Heterogeneous Water Splitting Catalysts - Craig, Michael John (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2023)
Understanding the sources of activity and stability in oxygen evolution reaction catalysts remains an open challenge. This thesis attempts to understand these factors by studying many catalysts for both homogeneous OER to glean high-level insights into the factors affording them high activity. First, we take 17 experimentally realized molecular catalysts and model the commonly assumed mechanism. Using principles derived from this work we attempt to screen for molecular catalysts with improved activity identifying Cr-based catalysts as a surprising potential option. We then focus specifically on Fe-based molecular catalysts and three inactive catalysts based on the same ligand framework but with Mn, Co, and Ni metal centres to understand the key differences which govern activity in these complexes. In heterogeneous catalysis, we focus on understanding how changes in metal oxidation state can influence stability in binary metal oxides. This leads to the development of a formation energy prediction scheme that is used to pre-screen mixtures of elements across the periodic table for active and acid-stable catalysts for the OER which are low-cost alternatives to the current catalysts based on precious metals.
APPROVED
Keywords: green technology; catalysis; high-throughput